TRAPS OF ENGLISH AS A TARGET LANGUAGE IN LEGAL TRANSLATION - CHROMÁ, Marta (Comparative Legilinguistics, 2016)
Translating legal texts into English requires that a translator should make a qualified decision with respect to a variety of legal English, or its modification, to be used as the target language. The analysis should be aimed at choosing the best possible “variety” of legal English at all “linguistic” levels – grammatical (morphology and syntax), semantic and conceptual (relevant terminological choice), textual (relevant text types/genres) and pragmatic (considering potential addressees). The decision relating to “which legal English” should be used may often be motivated by the type of target legal system (e.g. common law, continental law, sharia, etc.) and by an envisaged ultimate recipient of the translated text (whether the recipient has any legal background, previous experience in legal transactions conducted in English, etc.). The paper deals with the relevant aspects of such decision-making and provides examples of both useful options and confusing alternatives.